146k views
15 votes
Solve each equation ​

Solve each equation ​-example-1
User Yazaki
by
5.5k points

2 Answers

13 votes
Answer: v = 5

Step-by-Step Solution:

=> -3(v + 4) = 2v - 37
= -3 * v - 3 * 4 = 2v - 37
= -3v - 12 = 2v - 37
= -3v - 2v = -37 + 12
= -5v = -25
= 5v = 25
=> v = 25/5 = 5

Therefore, v = 5
User Ilgaar
by
6.4k points
5 votes

Explanation:

-3(v+4)=2v-37

-3v-12=2v-37

-12+37=2v+3v

25=5v

25/5=v

v=5

User James Evans
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.